Pelindungan Songkok Recca To Bone Sebagai Upaya Mendorong Perekonomian Pelaku Usaha Mikro, Kecil, dan Menengah - Mahmud, Muh. Thorieq Erzulsyah; Palar, Miranda Risang Ayu; Rafianti, Laina (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study discusses the importance of the protection of the Indication of Source for the Songkok Recca To Bone product from Bone Regency, South Sulawesi, which serves as both a local cultural identity and an economic asset for Micro, Small, and Medium Enterprises (MSMEs). Referring to Law No. 20 of 2016 on Trademarks and Indications of Source, this research examines the relationship between legal protection and local economic development to prevent violations and misuse of local products. Using normative legal and sociological methods, data was gathered through literature review and interviews. The findings indicate that protection of the Indication of Source positively impacts the MSMEs economy by marking products with origin labels. However, its implementation remains suboptimal due to the lack of support from the local government in monitoring and product registration. Recommendations include enhancing the local government's role in supporting MSMEs through data collection and formal protection to improve the competitiveness of products in the market.